Supervision in social work – implementation phase in the reform process of the system of social and child protection in Republic of Мontenegro - Jankovic, Ugljesa; Ilić, Vladimir (Ревија за социјална политика/Journal of Social Policy, 2018)
In the current context of the reform of social and child protection in Montenegro, the corresponding model of supervision should take into account the real professional and institutional capacities. The created model of supervision corresponds to the Anglo-Saxon tradition in the implementation of supervisory support. This paper examines the functionality of the current implementation process of the supervisory support to the professional workers in the centers for social work in Montenegro. Analysis of the characteristics of the supervision process is based on data and information collected through the analysis of laws, regulations and expert reports, direct observation of the work of professional staff of the center for social work, field visits and interviews with employees of the Institute of Social and Child Protection. Problems identified in the allocation of competencies, scope of work and clarity significantly limit the role of the supervisory process. In the countries with a developed practice of supervision clarity of roles and responsibilities of individual actors is achieved through a process that clarifies the purpose and boundaries of supervision. If the model of supervision does not meet the standards that guarantee the effectiveness and flexibility in providing customer service, then such a model does not guarantee sustainability of system in the long term. In conclusion are recommended guidelines for the further development of an appropriate model of supervision in social work centers in Montenegro.
Keywords: interior supervision; exterior supervision; decentralization; social protection; social services